Adaptability and growth of Hippocampus kuda and Oryzias melastigma under rapid temperature changes - Xu, Yongjian; Lin, Penghong; Zhang, Wenxin; Pan, Xia; Lu, Jun; Bo, Yang (Frontiers in Physiology, 2024)
Temperature changes had a huge impact on the growth of aquaculture organisms, which mainly involved two parameters: the changing amplitude and the changing speed.Wide-adaptability and narrowadaptability were divided by the amplitude,while fast-adaptability and slow-adaptability proposed in this article were divided based on the speed.Investigating the impact of the changing speed on artificial farming was vital. In this study,two fish species of wide-adaptability,Hippocampus kuda and Oryzias melatigma,were selected as research objects,explored the effects of temperature changing speeds on them under 2 changing amplitudes of 2℃ and 4℃.The similarities and differences in their responses to temperature changes were analyzed and compared from the aspects of feeding,metabolism,physiology,immunity,and growth. The results showed that all 3 changing speeds (0.5℃/h,1℃/h,and direct input) had no effect on the growth of O.melatigma under the 2 ℃ amplitude,while there were significant differences in various aspects of H.kuda in the treatments with the speeds between 0.5 ℃/h and direct input,such as a significant difference in growth,in food intake,and in response speeds and response levels of several enzymes and related genes.Under 4℃ amplitude,the impact of all 4 changing speeds (0.5℃/h, 1℃/h, 2℃/h and direct input) on both fish was more pronounced.H. kuda showed a significant difference of growth among 3 groups,and the critical safe speed was about 0.5℃/h in its heating treatments. And the growth decrease only occured the heating treatment of direct input in O. melatigma.Furthermore, some genes responded quickly and efficiently to the low-speed changes of temperature in H. kuda, but were inhibited in the treatments with high-speed changes.However, they can still express rapidly and efficiently in the high-speed treatments of O. melatigma, included several stress-related genes, lipid metabolic-related genes, and immune-related genes. Seen from these differences, the energy source used in H. kuda to resist stress was single and short-lived. So, under a long-term stress, H. kuda gradually transformed from normal physiological stress into pathological stress, leading to the outbreak of diseases.Therefore, for precise aquaculture of H. kuda, stricter and more precise control of environmental temperature is necessary to prevent rapid and big temperature changes from affecting the growth and survival of the seahorse.